Implementation Of Standard Operating Procedures In Handling Guest Check In and Check Out At Ayana Resort Bali - Wirya, I Made Suwitra; Widiantara, I Gusti Agung Bagus; Budiasa, I Ketut (Jurnal Manajemen Pelayanan Hotel, 2024)
This research was conducted in the front office department at Ayana Resort Bali, which discusses the implementation of standard operating procedures in handling check in and check out guests. This research is motivated by the existence of problems when handling check in and check out. So this research aims to find out the standard operating procedures for handling check in and check out as well as to find out how the implementation of standard operating procedures for handling check in and check out guests at Ayana Resort Bali. Researchers used primary data and secondary data to support this research. This research uses data collection techniques in the form of observation, interviews and documentation recording. The analysis technique used is a qualitative descriptive analysis technique that describes the comparison between the overall data obtained with the reality that occurs at the research site. The results of this study indicate that there are 5 (five) procedures out of 11 (eleven) standard operating procedures for handling check in that are not appropriate and 3 (three) procedures out of 13 (thirteen) standard operating procedures for handling check out that are not appropriate. Evaluation of the procedure along with the training needs to be done again in order to make the implementation of the SOP better than before.